Corporate Computer and Network Security / Second Edition - Panko Raymond R (Prentice Hall, 2010)
Preface, The Threat Environment: Attackers and theit Attacks, Planning, The Elements of Cryptography, Cryptographic System Standards, Access Control, Firewalls, Host and Data Security, Application Security, Incident and Disaster Response, Networking Concepts, Glossary, Index.